The risk of Plasmodium vivax parasitaemia after P. falciparum malaria: An individual patient data meta-analysis from the WorldWide Antimalarial Resistance Network - Hossain, Mohammad S. (2020)
WorldWide Antimalarial Resistance Network (WWARN), Oxford, United Kingdom, Global Health Division, Menzies School of Health Research and Charles Darwin University, Darwin, Australia, Centre for Epidemiology and Biostatistics, Melbourne School of Population and Global Health, The University of Melbourne, Melbourne, Victoria, Australia, International Centre for Diarrheal Diseases and Research, Bangladesh (icddr,b), Dhaka, Bangladesh.